Testosterone Deficiency Associated with Poor Glycemic Control in Korean Male Diabetics - Joo-Sung Kim; Bong Sun Kim; Ja Young Jeon; Yong Jun Choi; Yoon-Sok Chung (Endocrinology and Metabolism, 2014)
BackgroundRecent studies have shown that men with diabetes have lower testosterone levels than healthy men. However, studies on the correlation between testosterone and diabetes are rare in Korea. We examined the relationship between testosterone deficiency and markers related to diabetes in adult Korean men.MethodsA total 464 men with diabetes who visited an outpatient clinic at Ajou University Hospital and had serum total testosterone and serum insulin levels measured between January 2000 and September 2013 were selected. Blood samples were collected after the subjects had fasted overnight. We divided the participants into testosterone deficient and normal groups. Testosterone deficiency was defined as having a serum total testosterone level <3.5 ng/mL.ResultsOf 464 subjects, 34.9% had a testosterone deficiency. The mean levels of fasting plasma glucose (P=0.007) and glycated hemoglobin (HbA1c; P=0.038) were significantly higher in the testosterone deficiency group than in the normal group. To clarify the relationship between serum total testosterone level and fasting plasma glucose or HbA1c values, Pearson's correlation test was performed. Fasting plasma glucose levels (r=-0.142, P=0.002) and HbA1c values (r=-0.097, P=0.040) showed a significant negative correlation with serum testosterone levels in men with diabetes.ConclusionMajor markers of diabetes that are associated with testosterone deficiency are fasting plasma glucose and HbA1c values. Poor glycemic control appears to be associated with testosterone deficiency in Korean men with diabetes.